El consumo de los artículos de opinión generados en los diarios la gaceta y la hora de la ciudad de Latacunga y la apreciación de los estudiantes de la carrera de comunicación social de la universidad técnica de Cotopaxi - Freire Taco, Víctor Hugo (2016)
This investigative analysis seeks to highlight the existence of consumption and evaluation youth of Communication at the Technical University of Cotopaxi to take the opinion articles of newspapers, The Gazette and The Hour of Latacunga. To identify the objectives was necessary to apply surveys to students of all levels, the results showed that most of them do not have reading habits, not consumption, in addition to lack of interest in the genre of opinion, feeling familiar with the internet when informed, otherwise respondents propose a variety of topics as observation technique, also used, explains that the writers and the press give priority to political and preventing spread of other issues that youth cheers….